Conceptual Changes of Students in Thermodynamics in Physical Chemistry Course Through The Implementation of Blended Learning - Afadil Afadil; Sitti Rahmawati; Suherman Suherman (Universitas Tadulako, 2021)
This study aims to determine the conceptual changes of students after participating in learning with a blended learning approach on Thermodynamics material. This research is a type of pre-experimental (pre-experimental design) with a One Group Pretest-Postest Design. The blended learning approach is applied using the Problem Based Learning model. The research sample was Class C Odd Semester 2019/2020 students which consisted of 34 students who programmed Physical Chemistry courses. The instrument used is a two-tier multiple choice test which includes concepts in Thermodynamics material which is equipped with a valid CRI. The blended learning approach is one approach that can be used that facilitates student activities in utilizing ICT through the delivery of materials, discussion of task completion, and training in the search for teaching materials on Thermodynamics material. The results showed that misconceptions still occur in every concept of Thermodynamics. The average reduction of misconceptions (MC) is 11.2%, the increase in the number of students to knowing concept (KC) classically is 19.2%, and the decrease in the number of students unknowing concept (UKC) is classically 8.1%. Students' conceptual changes to the material of Thermodynamics are still low. Students are required to understand well the content of the material related to basic concepts, mathematical equations (formulas), and the applicative forms of concepts in everyday life in accordance with the characteristics of the thermodynamic material.